The flavonoid content and antiproliferative, hypoglycaemic, anti-inflammatory and free radical scavenging activities of Annona dioica St. Hill - Formagio Anelise S N; Kassuya Candida A L; Neto Frederico Formagio; Volobuff Carla R F; Iriguchi Edna K K; Vieira Maria do C; Foglio Mary Ann (BMC, 2013)
Abstract Background Annona dioica St. Hill (Annonacaeae) is a Brazilian plant used in folk medicine for the treatment of several types of rheumatisms and diarrhoea. The focus of this work was to evaluate the in vitro antiproliferative and antioxidant activity and the in vivo hypoglycaemic and anti-inflammatory activity of A. dioica and identify the principal constituents of this plant. Methods The crude methanol extract (EAD) and hexane (HF), chloroform (CF), ethyl acetate (EAF) and hydromethanol fractions (HMF) were evaluated for free radical scavenging activity using the DPPH assay. The EAD and EAF were assayed for hypoglycaemic activity in rats. The EAD was tested in an antiproliferation assay and for anti-inflammatory effects in paw oedema, in addition to myeloperoxidase activity induced by carrageenan (Cg) in mice. The EAF was assayed using chromatographic methods. Results The fractionation of the EAF through chromatographic methods identified derivatives of the flavonoids quercetin and kaempferol. Among all the tested fractions, the ethyl acetate and hydromethanol fractions were the most potent, exhibiting an IC50 of 8.53 and 10.57 μg/mL, respectively, which is comparable to that of the commercial antioxidant butylated hydroxytoluene (BHT). The oral administration of the EAD (100 mg/kg) and EAF (15 mg/kg) inhibited the increase of glucose levels, resulting in a hypoglycaemic effect. The EAD (30 to 300 mg/kg) exhibited an anti-oedematogenic effect in Cg-induced paw oedema in a time- and dose-dependent manner. The results showed a reduction of MPO activity by A. dioica 6 h after the induction of paw oedema at all doses tested with maximal inhibition at 300 mg/kg. Conclusions Our results reveal for the first time that compounds contained in the A. dioica leaves exert anti-inflammatory, hypoglycaemic, antiproliferative, and antioxidant effects. The antioxidant activity may be associated with the presence of flavonoids.